Case Report: Organic Hallucinosis in Viral Encephalitis - Andrian Fajar Kusumadewi (HM Publisher, 2021)
Introduction: Organic mental disorders are diseases we need to put more attention to because they are related to systemic disorders or disorders of the brain and can cause high mortality. Organic mental disorders often manifest in the form of psychiatric symptoms so that they can be treated too late because the physician is not able to recognize the symptoms which can be fatal. Sequelae can be found in organic mental disorders and may affect the patient’s quality of life, so fast and proper management is needed to get a better outcome. Case presentation: A case of organic hallucinosis in viral encephalitis had been reported in an 18-year-old male with a history of sudden changes in behavior. The symptoms appeared after the patient had problems during OSPEK and was threatened by someone. The patient was the only child in the family and was often spoiled by his parents. Laboratory and imaging studies showed that there was a cerebritis in the CT scan result, a decrease in CD4 count, and an increase in anti-Rubella IgG titers in which the patient was finally diagnosed with viral encephalitis. Conclusion: The diagnosis of organic mental disorders can easily be overlooked in daily clinical practice so patients do not receive proper management.